1988
DOI: 10.1042/bj2500797
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ornithine decarboxylase and antizyme activities in developing mouse brain

Abstract: A macromolecular inhibitor to ornithine decarboxylase (ODC) present in mouse brain was identified as ODC antizyme [Fong, Heller & Canellakis (1976) Biochim. Biophys. Acta 428, 456-465; Heller, Fong & Canellakis (1976) Proc. Natl. Acad. Sci. U.S.A. 73, 1858-1862] on the basis of kinetic properties, Mr and reversal of its inhibition by antizyme inhibitor. The brain antizyme, however, did not cross-react immunochemically with any of seven monoclonal antibodies to rat liver antizyme. ODC activity in mouse brain ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In the whole mouse brain, ODC catalytic activity is highest at birth and declines rapidly to a low adult level by postnatal day 21, while free AZ activity increases after birth [24], These results indicate that AZ may play an important role in the regulation of ODC activity and polyamine levels in the developing brain. Expression of ODC mRNA in developing mouse whole brain [25] and in rat cortex and cerebellum [20] has been described but there has been no study of the region-specific ontogenic pattern of ODC and particularly its relationship to antizyme gene expression.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the whole mouse brain, ODC catalytic activity is highest at birth and declines rapidly to a low adult level by postnatal day 21, while free AZ activity increases after birth [24], These results indicate that AZ may play an important role in the regulation of ODC activity and polyamine levels in the developing brain. Expression of ODC mRNA in developing mouse whole brain [25] and in rat cortex and cerebellum [20] has been described but there has been no study of the region-specific ontogenic pattern of ODC and particularly its relationship to antizyme gene expression.…”
Section: Introductionmentioning
confidence: 64%
“…An inverse relationship between ODC and antizyme activity during development has been reported in the brain [24]. Antizyme activity is low at birth but increases about 7-fold by 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that the physiological ODC activity in these organs is repressed by distal silencer elements that were not included in the transgene construct. The expression of AZ also varies in different parts of the adult brain largely paralleling the expression of ODC (9,13). A third variant of AZ, antizyme 3 (AZ3), was recently cloned and found to be exclusively expressed in the testes (14).…”
mentioning
confidence: 99%
“…After cerebral ischemia ODC is up-regulated also in regions where no cellular damage usually occurs (Keinänen et al, 1997). In mammalian brain, ODC activity is highest at birth and thereafter declines during the first weeks or months to a low adult level (Laitinen et al, 1982;Onoue et al, 1988;Morrison et al, 1998), although the amount of immunoreactive enzyme is still relatively high (Laitinen et al, 1985). In the adult brain a large amount of ODC is bound to the Az as an inactive complex and it has been suggested that the bound ODC represents the storage form of the enzyme that can be rapidly activated by dissociation for local needs (Laitinen et al, 1985(Laitinen et al, , 1986.…”
mentioning
confidence: 99%